Systemic Inflammatory Response in Brain Injury - D. V. Vyalov; N. V. Nikiforova; Yu. A. Churlyaev (Общая реаниматология, 2007)
Objective: to study the specific features of a systemic inflammatory response in critical ill patients with brain injury.Subjects and methods. A hundred and nine patients were examined. Of them, there were 60 apparently healthy donors who formed a control group (whose obtained values were taken as normal) and 49 patients with isolated severe brain injury in the acute period. The magnitude of a systemic inflammatory response was evaluated from the blood levels of acute-phase response agents, such as C-reactive protein, haptoglobin, a^-antitrypsin, ceruloplasmin, transferrin, proteins of complement C3, C4, albumin.Results. Analysis of the findings revealed that the systemic inflammatory response developed in severe brain injury, but it had its own features. Thus, there was a less increase in the level of C-reactive protein and a decrease in the blood concentrations of the positive acute-phase response agent haptoglobin. The change in the content of the other study acute-phase proteins was the same as described for a classical systemic inflammatory response in septic states and during surgical intervention.Conclusion. The revealed changes in the levels of C-reactive protein and haptoglobin support the view of limitation of a brain lesion focus by the functioning blood-brain barrier, by determining the course of a systemic inflammatory response in patients with severe brain injury.